Penerapan Media Papan Labirin Untuk Meningkatkan Kemampuan Berhitung Pada Materi Penjumlahan Bilangan Kelas 1 - Asnidar; Mushlihuddin, Rahmat; Nasution, Afrida Hanum (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to determine the application of labyrinth board media on the addition of material to improve students' arithmetic skills in class 1 of SDN 060913 Medan. The research design used is Classroom Action Research (CAR). The subjects of this study were students of class IA SDN 060913 Medan, totaling 24 students consisting of 12 male students and 12 female students. Data collection techniques in the study were carried out by observing teacher and student activities, tests, and documentation. The results of the study showed that the application of labyrinth board media can improve the arithmetic skills of class I students of SDN 060913 Medan, this can be seen from the average score in cycle I, which is 68.75 with a percentage of 46%. In cycle II, it has started to increase with an average score of 85 with a percentage of 87.5%. The application of the labyrinth board media used makes students practice questions so that they can remember what they have learned. So it can be concluded that the application of labyrinth board media in addition material can improve the arithmetic skills of class 1A students at SDN 060913 Medan.